Becoming and being a parent with an inherited predisposition to diffuse gastric cancer: A qualitative study of young adults with a CDH1 pathogenic variant. Issue 3 (4th May 2023) - Tutty, Erin; Forbes Shepherd, Rowan; Hoskins, Cass; Purvis, Rebecca; Shanahan, Mary; Boussioutas, Alex; Forrest, Laura E.
Abstract: Purpose: This study explored the experiences of young people with hereditary diffuse gastric cancer (HDGC), an inherited cancer predisposition syndrome, as they navigate becoming and being a parent. Design: We used interpretive description and conducted semi-structured interviews with 13 young Australians (18–39 years) with a CDH1 pathogenic variant (PV). Data were analyzed using team-based, reflexive thematic analysis. Findings: Participants' reproductive decisions centered on the perceived manageability of HDGC, namely via gastrectomy, and timing of their genetic testing. Participants yet to have children and those with challenging gastrectomy experiences favored using reproductive technologies to prevent passing on their PV. Parents who had children before genetic testing described complicated decisions about having more children. Gastrectomy was considered a parental responsibility but recovery diminished parenting abilities. Conclusion: Young people with HDGC face unique challenges navigating reproductive decision-making and parenting with gastrectomy. Findings lend credence to calls for longitudinal, developmentally sensitive genetic counseling services.